Real-time cationic sensing using plasmonic fiber optic sensor based phosphoryl-carrageenan - Abu Bakar, Mohd Hafiz; Azeman, Nur Hidayah; Mobarak, Nadhratun Naiim; Ahmad Nazri, Nur Afifah; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Dzulkefly Zan, Mohd Saiful; Mahdi, Mohd Adzir; Md Zain, Ahmad Rifqi; Gupta, Ruchi; Abdullah, Fairuz; A. Bakar, Ahmad Ashrif (Elsevier B.V., 2024)
We report Fiber Optic-Localized Surface Plasmon Resonance (FO-LSPR) spectroscopy sensors comprising a coating of spherical silver nanoparticles (AgNPs) embedded in phosphoryl-carrageenan. This is a novel report on modified carrageenan namely phosphoryl-carrageenan as sensing materials for cations specifically ammonium ions (NH4+). The morphology of carrageenan and phosphoryl-carrageenan coatings on the fiber optic probe was uneven and wavelike topography, indicating the successful coating on the fiber optic probe surface. The FO-LSPR showed a distinct dip in reflectivity in the region of 370–400 nm due to the resonance frequency of spherical AgNPs. The response and recovery times of FO-LSPR sensors for 1 ppm NH4+ and deionized water were <20 s and ∼1.2 minutes, respectively, with five times stable repeatability. The sensitivity of the FO-LSPR phosphoryl-carrageenan was 3.441 nm/ppm. Equally, the limits of detection and quantitation of fiber optic FO-LSPR were 0.336 and 1.018 ppm, respectively. Meanwhile, the dynamic range of the FO-LSPR was 0.3 – 2.0 ppm. The proposed sensor demonstrated strong selectivity towards NH4+ over common cationic interferents. Furthermore, the reported FO-LPSR sensor offered a comparable measurement performance to current methods, while being low cost and portable, and allowing in-situ real-time monitoring of cation ammonium. Thus, reported FO-LPSR sensors are highly promising for water monitoring applications.